IMPLEMENTASI KEBIJAKAN PENGELOLAAN BARANG MILIK DAERAH PADA PEMERINTAH KABUPATEN MINAHASA - Lumingkewas, Elvis; Supit, Brain Fransisco (Academy of Education Journal, 2023)
This study expects to portray and break down the most common way of getting ready Local Regionall Property Needs Plans (RKBMD) by Territorial Devices in Minahasa Regime. This study utilized subjective examination techniques. The administration of local property in the Minahasa Rule Government, for this situation the readiness of the Regionall Property Needs Plans (RKBMD) in the Minahasa Regime Government, has not worked out positively. This is a direct result of the 4 (four) perspectives contemplated, it makes sense of that the primary hindrance in the correspondence viewpoint is socialization, when seen from the fundamental asset viewpoint it very well may be presumed that the absence of human and monetary assets is a deterrent in the asset perspective, and in The demeanor angle should be visible from the absence of mindfulness in doing liabilities as an authority overseeing territorial property and from the part of regulatory construction where there is an absence of comprehension of SOPs in regards to the readiness of Regionall Property Needs Plans (RKBMD).